2018
DOI: 10.1007/s10909-018-2018-9
|View full text |Cite
|
Sign up to set email alerts
|

Mexico-UK Sub-millimeter Camera for Astronomy

Abstract: MUSCAT is a large format mm-wave camera scheduled for installation on the Large Millimeter Telescope Alfonso Serrano (LMT) in 2018. The MUSCAT focal plane is based on an array of horn coupled lumped-element kinetic inductance detectors optimised for coupling to the 1.1mm atmospheric window. The detectors are fed with fully baffled reflective optics to minimize stray-light contamination. This combination will enable background-limited performance at  = 1.1 mm across the full 4 arcminute fieldof-view of the LMT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
(11 reference statements)
1
13
0
Order By: Relevance
“…From this calculated mapping sensitivity, we find a simulated mapping speed of 0.63 deg 2 /mJy 2 /h for the scan rate of 400 s −1 . This simulated mapping speed is comparable to the theoretically calculated mapping speed of 3.0 deg 2 /mJy 2 /h reported by Castillo-Dominguez et al 17 using a purely bolometric model scaled by the factor ∼ 7 found by comparing the bolometric mapping speed of the AzTEC camera to the observed performance on sky at the James Clark Maxwell (JCMT) telescope. 18 Scaling Castillo-Dominguez et al's mapping speed by this factor gives a mapping speed of 0.42 deg 2 /mJy 2 /h.…”
Section: Simulation Resultssupporting
confidence: 86%
“…From this calculated mapping sensitivity, we find a simulated mapping speed of 0.63 deg 2 /mJy 2 /h for the scan rate of 400 s −1 . This simulated mapping speed is comparable to the theoretically calculated mapping speed of 3.0 deg 2 /mJy 2 /h reported by Castillo-Dominguez et al 17 using a purely bolometric model scaled by the factor ∼ 7 found by comparing the bolometric mapping speed of the AzTEC camera to the observed performance on sky at the James Clark Maxwell (JCMT) telescope. 18 Scaling Castillo-Dominguez et al's mapping speed by this factor gives a mapping speed of 0.42 deg 2 /mJy 2 /h.…”
Section: Simulation Resultssupporting
confidence: 86%
“…The SuperSpec coupling optics consist of the warm mirrors under development for MUSCAT, 13 along with a subsequent set of 5 warm mirrors, and a single cold lens ( fig. 9).…”
Section: Deployment At the Lmtmentioning
confidence: 99%
“…The MUSCAT cooling chain is illustrated in Figure 1a. The full mechanical design of the MUSCAT cryostat is described by Castillo-Dominguez et al 1 but is outlined in Figure 1b. The third and fourth temperature stages of MUSCAT (the first two not cooled by the pulse tube cooler) are cooled by continuous sorption (CS) coolers.…”
Section: Cooling Chainmentioning
confidence: 99%
“…To verify the plausibility of the cooling chain presented here, we have modelled the expected thermal load on each stage of MUSCAT, the results of this are presented in Table 1. A complete description of the structure and interfaces between stages is given by Castillo-Dominguez et al 1 The total required volume of He 3 in MUSCAT is approximately 9 L STP of gas. This consists of 4 litres in the 450-mK cooler pumps, 1.5 litres in each of the continuous soprtion ballast tanks, and 2 litres in the miniature dilutor.…”
Section: Thermal Supportsmentioning
confidence: 99%